TEACHER'S STRATEGY IN CREATING EFFECTIVE CLASSROOM MANAGEMENT - Anna Ismawati; Neviyarni Suhaili; Herman Nirwana (Literasi Nusantara, 2021)
This article discusses Teacher Strategies in Creating Effective Classroom Management using references from relevant literature studies. Classroom management refers to the skills and strategies used by teachers to optimize learning in the classroom. Classroom management principles that can be used include; a) Warm and enthusiastic, b) Challenge, c) Varied, d) Flexibility, e) Emphasis on positive things, and f) Instilling self-discipline. The principles of classroom management can be implied by the teacher in the learning process. The Implementation Strategies for the Principles of Class Management are: a) Exemplary, b) Habituation, 3) Starting stories or examples, d) Applied through the.curriculum.